Respuestas
Respuesta dada por:
1
7 +6x: 13
13-7: 6x
13-7: 6
6x/6: 1x
x:1
Respuesta dada por:
0
Hola,
![7x + 6x = 13 7x + 6x = 13](https://tex.z-dn.net/?f=7x+%2B+6x+%3D+13)
Resolvemos la ecuación:
![7x + 6x = 13 \\ 13x = 13 \\ x = \frac{13}{13} \\ x = 1 7x + 6x = 13 \\ 13x = 13 \\ x = \frac{13}{13} \\ x = 1](https://tex.z-dn.net/?f=7x+%2B+6x+%3D+13+%5C%5C+13x+%3D+13+%5C%5C+x+%3D++%5Cfrac%7B13%7D%7B13%7D++%5C%5C+x+%3D+1)
Solución:
![x = 1 x = 1](https://tex.z-dn.net/?f=x+%3D+1)
Espero que te sirva, Saludos.
Resolvemos la ecuación:
Solución:
Espero que te sirva, Saludos.
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años